(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The novel "Water," produced in 2006, sheds attention on the controversial topics of patriarchy, widowhood, and child prostitution in pre-partition India. This study examines the process of widows adapting to life in Ashram, an often frequented place along their migratory paths.